1993
DOI: 10.1021/ic00071a023
|View full text |Cite
|
Sign up to set email alerts
|

Bond valence sum analysis of metal-ligand bond lengths in metalloenzymes and model complexes. 2. Refined distances and other enzymes

Abstract: The bond valence sum (BVS) method is further applied to metalloenzyme active sites. When a particular coordination model is assumed, the BVS method allows for oxidation states of metal ions in metalloproteins to be determined from metal-ligand bond distances measured using extended X-ray absorption fine structure (EXAFS) analysis. Thus, the BVS can be used to determine the compatibility between a given coordination model and a particular oxidation state. A new procedure for calculating ro values on which BVS's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
442
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 785 publications
(481 citation statements)
references
References 2 publications
34
442
0
2
Order By: Relevance
“…Table 1 summarizes the optimized R 0 parameters for iron(II) and iron(III), estimated using both homoleptic and heteroleptic metal-binding sites within the first coordination sphere, and compares them with several previous studies (Brese & O’Keeffe, 1991; Liu & Thorp, 1993; Kanowitz & Palenik, 1998). While most of the R 0 parameters derived here for iron agree within ±0.1 Å with previously reported values, we found that the Fe—N R 0 parameters reported previously appear to agree well only with the corresponding high-spin (HS) species.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Table 1 summarizes the optimized R 0 parameters for iron(II) and iron(III), estimated using both homoleptic and heteroleptic metal-binding sites within the first coordination sphere, and compares them with several previous studies (Brese & O’Keeffe, 1991; Liu & Thorp, 1993; Kanowitz & Palenik, 1998). While most of the R 0 parameters derived here for iron agree within ±0.1 Å with previously reported values, we found that the Fe—N R 0 parameters reported previously appear to agree well only with the corresponding high-spin (HS) species.…”
Section: Resultsmentioning
confidence: 97%
“…The few reports including heteroleptic sites do employ optimization techniques, nonetheless they are based on a small selection of manually chosen structures (Liu & Thorp, 1993). The method we adopted allows the simultaneous refinement of multiple R 0 parameters based on a large set of varied structures, including heteroleptic binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…fits 3 to 6, Table 2). Bond valence sum (BVS) analysis is an empirical method for correlating the sum of the strength of the metalligand bonds, as measured by the bond length, to the oxidation state of the metal (40,57). BVS confirms that the Zn site has a coordination number of 4 (the BVS value should be approximately equal to the oxidation state of the metal, i.e., 2).…”
Section: Analytical Ultracentrifugation Analysismentioning
confidence: 99%